Fabrication of Fe3O4/O‐Carboxylmethyl Chitosan Magnetic Particle Assembles in Inverse Miniemulsions for Loading and Release of Bovine Serum Albumin. Issue 27 (21st July 2020) - Gao, Feng; Qi, Qi; Liang, Xiaoqin; Wen, Lixin; Shang, Yi; Mi, Yifang; Ziener, Ulrich; Cao, Zhihai
Abstract: Fe3 O4 / O ‐carboxylmethyl chitosan (OCMC) magnetic particle assembles (MPAs) with high magnetite loading and superparamagnetism were controllably prepared through Schiff base crosslinking reaction of OCMC‐stabilized Fe3 O4 magnetic nanoparticles (OCMC‐Fe3 O4 MNPs) in the dispersed phase of inverse miniemulsions. The Fe3 O4 /OCMC MPAs were composed of many tiny Fe3 O4 MNPs, and they did not only inherit the good superparamagnetism of OCMC‐Fe3 O4 MNPs, but also displayed high collective magnetic response to an external magnetic field. The crosslinked network of OCMC offered a good structural integrity of the Fe3 O4 /OCMC MPAs either in inverse emulsions or in aqueous dispersions within a wide pH range. The Fe3 O4 /OCMC MPAs displayed a reversible pH‐dependent loading and release behavior of a model protein, bovine serum albumin, exhibiting a great potential in functioning as nanocarriers for loading and release of biomacromolecules. Abstract : In this work, Fe3 O4 / O ‐carboxylated chitosan (OCMC) magnetic particle assembles (MPAs) with high magnetite loading and superparamagnetism were facilely and controllably prepared through self‐assembly of OCMC‐stabilized Fe3 O4 magnetic nanoparticles and followed Schiff base crosslinking reaction in the dispersed phase of inverse miniemulsions. The prepared Fe3 O4 /OCMC MPAs displayed a reversible pH‐dependent loading and release behavior of a model protein, bovine serum albumin.